PENGARUH PROFITABILITY, LEVERAGE DAN BOARD DIVERSITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 - 2019 - Siti Nurlatifah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This study aims to analyze the effect of profitability, leverage and board diversity on tax avoidance. Measurement of tax avoidance in this study uses the cash effective tax rate (CETR). This study uses data from companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The number of research samples as many as 10 companies obtained by purposive sampling method. The data source of this research is secondary data, in the form of an annual report. The analytical technique used in this research is multiple linear regression analysis. The results of the analysis show that profitability (X1) has no effect on tax avoidance, leverage (X2) has an effect on tax avoidance and board diversity consisting of: female board of directors (X3), age of the board of directors (X4) and educational background of the board of directors (X5 ) has no effect on tax avoidance.